Detection of Khapra Beetle Environmental DNA Using Portable Technologies in Australian Biosecurity - Trujillo-González, Alejandro; Thuo, David N.; Divi, Uday; Sparks, Kate; Wallenius, Thomas; Gleeson, Dianne (Frontiers in Insect Science, 2022)
Khapra beetle, Trogoderma granarium Everts, 1898, is a serious pest of stored grain products globally. Environmental DNA (eDNA)-based methods offer sensitive detection tools used to inform biosecurity officers on the presence of high-risk pests. This study tested laboratory and portable molecular technologies to detect khapra beetle environmental DNA extracted from dust samples collected during biosecurity responses (Tuggeranong and Fyshwick) to khapra beetle incursions in Australia. Airborne and floor dust samples were collected opportunistically using handheld vacuum cleaners and eDNA was extracted using either field or laboratory-based extraction methods and analysed using laboratory benchtop real time PCR machines and portable machines with two TaqMan and one LAMP-based assay. We successfully collected, extracted, and amplified khapra beetle eDNA from dust samples by qPCR, but failed to amplify T. granarium eDNA using LAMP. The Laboratory qPCR machine showed significantly higher mean Ct values (p <0.001) and significantly higher positive detections for both assays (p <0.001) compared to the portable thermocycler. DNA yield was significantly higher in samples extracted using laboratory-based kits compared to field kits (p< 0.001) for both vacuumed and airborne samples (Mean DNA ± S.D. = 5.52 ± 4.45 and 4.77 ± 1.68 ng/µL, respectively), compared to field kits, (1.75 ± 1.17 and 1.36± 1.29 ng/µL for vacuumed and airborne samples, respectively). There were no significant differences in DNA yield between collection methods or differences in amplification associated to extraction or collection methods in either platform tested in this study. Portable technologies tested in this study (Franklin™ Real Time Thermocycler and Genie III) accurately amplified all tissue derived DNA during assay optimisation and field testing, highlighting the capacity of these technologies to complement biosecurity in confirming specimen ID. There was a high incidence of positive detections in field negative controls (Tuggeranong = 12.3 % and Fyshwick =50 %), mostly attributed to the use of contaminated vacuum cleaners. We discuss suitable methods to minimize sample cross-contamination, the potential of portable molecular technologies as tools for biosecurity applications, and the suitability of eDNA-based molecular detection methods to complement global trade biosecurity for one of the most invasive and important grain pests worldwide.